Health economic analysis of laparoscopic lavage versus Hartmann's procedure for diverticulitis in the randomized DILALA trial. Issue 11 (22nd August 2016) - Gehrman, J.; Angenete, E.; Björholt, I.; Bock, D.; Rosenberg, J.; Haglind, E.
Abstract: Background: Open surgery with resection and colostomy (Hartmann's procedure) has been the standard treatment for perforated diverticulitis with purulent peritonitis. In recent years laparoscopic lavage has emerged as an alternative, with potential benefits for patients with purulent peritonitis, Hinchey grade III. The aim of this study was to compare laparoscopic lavage and Hartmann's procedure with health economic evaluation within the framework of the DILALA (DIverticulitis – LAparoscopic LAvage versus resection (Hartmann's procedure) for acute diverticulitis with peritonitis) trial. Methods: Clinical effectiveness and resource use were derived from the DILALA trial and unit costs from Swedish sources. Costs were analysed from the perspective of the healthcare sector. The study period was divided into short‐term analysis (base‐case A), within 12 months, and long‐term analysis (base‐case B), from inclusion in the trial throughout the patient's expected life. Results: The study included 43 patients who underwent laparoscopic lavage and 40 who had Hartmann's procedure in Denmark and Sweden during 2010–2014. In base‐case A, the difference in mean cost per patient between laparoscopic lavage and Hartmann's procedure was €–8983 (95 per cent c.i. –16 232 to –1735). The mean(s.d.) costs per patient in base‐case B were €25 703(27 544) and €45 498(38 928) for laparoscopic lavage and Hartmann's procedure respectively, resulting in a difference of €–19 794 (95 per cent c.i. –34 657 to –4931). The results were robust as demonstrated in sensitivity analyses. Conclusion: The significant cost reduction in this study, together with results of safety and efficacy from RCTs, support the routine use of laparoscopic lavage as treatment for complicated diverticulitis with purulent peritonitis. Abstract : In favour of lavage